DIMENSION AND SUBJECTIVITY OF THE MATHEMATICAL SIMULATION ASSESSMENTS FOR THE FORECAST OF THE AVIATION SAFETY LEVEL - Юн, Геннадій Миколайович; Валько, Алла Миколаївна; Борець, Ірина Валеріївна (Science-based technologies, 2019)
It is established that International aviation organizations are constantly tightening requirements and demand to improve the technical and technological support of processes of control for aviation safety (AB) when the passenger service and baggage handling. However, the level of technical equipment of the airports, but there are new methods and means of implementing acts of unlawful interference which jeopardize the safe operation of civil aviation. The article presents an overview of mathematical modeling during the formalization of the subject area related to aviation security in civil aviation. and refined the concept of "aviation safety". The mathematical models to evaluate the level of aviation safety of the airport, namely: the mathematical model of the "risks" of ABA and the mathematical model of the "vulnerability" of ABA, based on qualimetric the models and use the analogy of the concepts of "quality" and "vulnerability" as well as a mathematical model for integrated air transport security. It is established that the prediction of individual performance and aviation safety in General, correctly be based on the work of highly skilled experts and the processing of their subjective evaluations, because most real events are characterized by some uncertainty, so each observation in the time series (factor) to assign a fuzzy variable with a certain membership function. Solving a scientific task of developing a mathematical model of interaction of airport services in emergency situations in Aeroporto the system defined by the system look for all calculations analyzed a mathematical simulation that provides high-quality analysis of a control system of the aviation security control in the passenger service and baggage handling.